PERILAKU IBU HAMIL DALAM MENJAGA KESEHATAN KEHAMILAN DI DESA PASAR BARU KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Titin Maya Puji Lestari; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Pregnancy and essentially natural nature should be run by the women and at the same time who could be a threat to the safety of her soul, in order to make it does not constitute a serious threat so pregnancy need help with good care. Prenatal care as a sub-system of health care is strongly associated with female reproductive functions so the attempt is determined by the behavior of herself.According to a theory that healthy behaviors can occur because of changes in the level of knowledge, attitudes and actions of the individual. All three of these factors will influence the behavior. Based on the explanation above, it is necessary to conduct a study to get an idea of the behavior of pregnant women in prenatal care. Pregnancy is a process of a woman's life which the presence of this process will lead the mother to a changes, which include changes in physical, mental, and social. In these changes it could not be separated from the factors that influence it, namely physical factors, psychological, environmental, social, cultural, and economic.This study aims to determine of how does the pregnant women keep the pregnancies Pasar Baru Village, Pangean, Kuantan Singingi Regency. What are the factors of failure of loan funds. The type of this research is simple random sampling with quantitative descriptive approach. The data which needs include primary data were obtained through the results of filling questioner and secondary data. The total of the population is 87 and the number of samples is 26 by 30%.Based on the results of this research it can known that the pregnant women had lack of knowledge in keeping her pregnancy, the confidence of concerning the prohibition of pregnancy was still high. Nutritional needs of pregnant women have been met and are still unmet. The willingness of mothers in caring a pregnancy was high enough.Keywords: Knowledge of pregnancy, and pregnancy ban factor